Identification of indole acetic acid biosynthesis pathways in Trichoderma asperellum and Trichoderma koningiopsis - Romero, Eliezer; Hernández, José; Gonzalez†, Juan; Hernández, Sanjuana; Oliva , Amanda; Quiroz, Jesús (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Trichoderm spp. produces secondary metabolites associated with plant growth promotion, especially the production of indole acetic acid (IAA), the main plant hormone. The tryptophan-dependent (TRP-D) and tryptophan-independent (TRP-I) production pathways, depending on the precursor involved in IAA synthesis, are well known. The objective of this study was to investigate the tryptophan-dependent (TRP-D) production pathway under in vitro liquid culture conditions (Potato Dextrose), supplemented with tryptophan (TRP). The presence of auxinic compounds in TRP-D was quantified using high-performance liquid chromatography (HPLC). Additionally, the morphology of corn seeds was analyzed using scanning electron microscopy (SEM). The interaction of Trichoderma spp. with corn seed germination was evaluated under controlled laboratory conditions, conducting the assay in triplicate and performing an analysis of variance (ANOVA). The results showed that the species T. asperellum and T. koningiopsis can degrade TRP and synthesize IAA through the tryptamine (TRM) and indole acetamide (IAM) pathways. However, IAA synthesis was not detected through the indole pyruvic acid (IPyA) and 3-indole acetonitrile (IAN) pathways. In particular, T. asperellum produced significantly higher concentrations of IAA compared to T. koningiopsis. Additionally, it was observed that tryptophan supplementation increased IAA production in both species. Finally, T. koningiopsis showed a strong relationship with the maize root system, invading the root and establishing a beneficial interaction that could contribute to plant growth and development. These findings suggest that T. koningiopsis has significant potential as a biofertilizer in agricultural systems.